The Correlation of Islam with Local Culture in the Kawin Cai Tradition in Sundanese Society - Dena Agustina; Wahyudin Darmalaksana; Busro Busro (Islam Transformatif : Journal of Islamic Studies, 2022)
This study aims to determine how the relationship between Islam and local culture in the Kawin Cai tradition of the Sundanese people. This research method  is a  field research by collecting data through observation, interviews, and documentation. The results of this study indicate that there is a mutually supportive correlation between Islam and local culture. The pattern of correlation between Islam and local culture can be seen from the implementation of the Kawin Cai tradition in the Jalaksana District community which contains Islamic values. Activities based on religious values in the Kawin Cai tradition include praying together, eating together and sharing among human beings. These activities have proven the correlation between Islam and local culture in Tatar Sunda, especially in Jalaksana District, Kuningan Regency. This study contributes to realizing harmony in society. It is hoped that the community will understand more and more that the implementation of local traditions is not always associated with shirk, but there is religious value in it. Such comprehension makes a significant contribution to the pluralistic society of Indonesia.